Sensitive and rapid detection of tetrodotoxin based on gold nanoflower-and latex microsphere-labeled monoclonal antibodies - Huang, Yongming; Xu, Aidi; Xu, Yang; Wu, Huijuan; Sun, Menghan; Madushika, Lakshani; Wang, Rongzhi; Yuan, Jun; Wang, Shihua; Ling, Sumei (Frontiers in Bioengineering and Biotechnology, 2023)
Tetrodotoxin (TTX) could result in serious disease due to its extremely high neurotoxicity Thus, it is of great importance to measure TTX for food safety. In this study, anti-TTX monoclonal antibody with good specificity and high affinity was used to develop the immunochromatography test strips. Gold nanoflowers (AuNF) with multiple branches and latex microspheres (LM) with large particle size as signal reporters were employed for improving the sensitivity of test strips. Both the AuNF and LM probes are stable and the developed immunochromatography test strips were specific to TTX, demonstrating no cross-reactivity with other marine toxins. The linear range of AuNF- and LM -based strips for TTX were 9.49-330.98 ng/mL and 5.40-443.19 ng/mL respectively. Limit of detection (LOD) of AuNF- and LM-based strips were determined to be 9.49 ng/mL and 5.40 ng/mL respectively. In summary, the development of immunochromatography test strips based on AuNF and LM signal probes displayed enhancement of sensitivity and provided rapid and specific detection of TTX.